A Mathematical Framework for Interpreting Playing Environments as Media for Information Flow. (12th October 2008) - Motoyoshi, Tatsuo; Hattori, Takashi; Kawakami, Hiroshi; Shiose, Takayuki; Katai, Osamu
Abstract : This paper proposes a novel strategy of designing play equipments. The strategy introduces two loose constraints as a guideline for designers. The first constraint is "describing unit of play action chain"〈 O, S, V 〉 based on Barthes' semiology, and the second is the infomorphism between designer, play equipment, and players based on channel theory. We provide detailed explanation of the strategy through an example of a designing process of playing environment where the players usage of the play equipment cannot be foreseen.